A SAÚDE BUCAL E A FITOTECNIA: AÇÕES INTERDISCIPLINARES DO ODONTÓLOGO E ENGENHEIRO AGRÔNOMO - Buffon, Marilene da Cruz Magalhães (Scientia Agraria, 2003)
This work aims to discuss and present a possible interdisciplinary relation between the dentist and the agronomy engineer, both focusing on the improvement of the rural populations quality of life, through preventive and educational measures that contributes to the citizenship construction, having in view the social and the environmental paradigm. It also aims to present the phytotherapy as an adequate therapeutics perspective. The analysis and synthesis new based on descriptive bibliographic research. The rural population, besides being excluded from epidemiological statistics, do not have access to basic health care. However this population do have, in most of the times, the agronomy engineer as an adviser and guide to their problems. Epidemiological studies show that caries and periodontal disease affect a large proportion of Brazilian inhabitants. These diseases are caused by plaque. The constant necessity to evaluate viable alternatives, which are cheap and safe, to the plaque control, has stimulated studies of medicinal plants to this issue. In rural areas, phytotherapy may be indicated as an alternative in preventive programs, through an dentist and an agronomist-educator, trying to change the agriculturists attitudes, promoting health improvement, and a better quality of life.